Ceratolejeunea panamensis (Lejeuneaceae, Marchantiophyta), a new species from Panama - Fossatti, Iris; Bastos, Cid José Passos; Benítez, Ángel (Phytotaxa, 2020)
Ceratolejeunea panamensis is described from Chiriquí province, Panama. The new species is distinguished from other species of the genus Ceratolejeunea by its numerous, scattered ocelli (6-20) in the leaf lobes and the very shortly bifid, reniform underleaves.